The emotional valence of a conflict: implications from synesthesia - Perry, Amit; Henik, Avishai (Frontiers in Psychology, 2013)
According to some synesthetes' reports, their experience involves an emotional sensation in which a conflict between the photism and presented color of a stimulus may evoke a feeling of discomfort. In order to investigate the impact of this experience on performance, two experiments were carried out on two synesthetes and their matched control groups. Experiments were tailored for each synesthete according to her unique photism. Participants were presented with stimuli (numerals or words) in colors and were asked to name the color of the stimulus and to ignore its meaning. Incongruent colors were associated with negative or positive emotional words or with non-emotional words. Not surprisingly, an incongruent color (e.g., 5 presented in yellow to a synesthete that sees 5 in red) slowed down color naming. Conflict situations (e.g., a numeral in an incongruent color) created a negative emotional experience. Most importantly, coherence between a conflict or non-conflict emotional experience and the emotion elicited by the color of the stimulus for a given synesthete modulated performance. In particular, synesthetes were faster in coherent than in incoherent situations. This research contributes to the understanding of emotional experience in synesthesia, and also suggests that synesthesia can be used as an instrument to investigate emotional processes in the wider population.